Characteristics and origin of desorption gas of a transitional shale: A case study from the Lower Permian Taiyuan Formation shale, Ordos Basin, northern China. (17th December 2017) - Xu, Liang; Wang, Yongli; Wei, Zhifu; Wu, Baoxiang; Zhang, Mingfeng; Wang, Gen; Sun, Zepeng
ABSTRACT: In China, marine shale and terrestrial shale have achieved significant breakthroughs. Comparing with marine shale and terrestrial shale, the research and exploration of transitional shale are still in the preliminary stage, and the content and origin of desorbed gas from transitional shales are poorly documented, thus limiting the understanding of gas generation and potential play elements. Geochemical characteristics of desorbed gas, including content and origin, are analyzed from 9 core samples of the Lower Taiyuan Formation shale from well SSL23 in the Ordos Basin, northern China. The results show that the Taiyuan Formation shale in the study area are characterized by high total organic carbon content of 2.70–9.00%, type III organic matter, and high Tmax ranging from 461 to 520°C. The desorbed gas content of the shale samples varies from 0.79 to 2.37 m 3 /t, with an average of 1.35 m 3 /t. The gases are dominated by hydrocarbons (83.72–98.62%), with small amounts of non-hydrocarbons (1.38–16.28%) and the methane is the dominant component of the desorbed gases. The carbon isotope δ 13 C1 ranges from −43.9 to −26.3 ‰, the δ 13 C2 ranges from −27.2 to −23.1 ‰ and the δ 13 C3 ranges from −25.3 to −11.6 ‰, respectively. The Whiticar chart and the plot of δ 13 C1 -δ 13 C2 suggest that gases released from the Taiyuan Formation shale are thermogenic in origin and possibly coal-derived.